“Ketidaksempurnaan Bukan Penghalang Untuk Meraih Prestasi”: Studi Analisis Fenomenologi Interpretatif Tentang Dinamika Hardiness Pada Remaja Tunadaksa Berprestasi Yang Tinggal Di Asrama SLB D YPAC Bali - Kusuma, Anak Agung Istri Candra Adnyawari; Susilawati, Luh Kadek Pande Ary (Peneliti.net, 2023)
Teenagers with disabilities who live in dormitories do face difficulties in accepting their physical conditions, which are far from ideal. However, many of them are still able to achieve accomplishments, even at the national level. Various issues experienced by these disabled teenagers living in dormitories require them to possess a personal characteristic that views everything as a challenge rather than an obstacle, which is referred to as hardiness. This study aims to explore the dynamics of hardiness among high-achieving disabled teenagers living in dormitories. The research method used in this study is qualitative research with a phenomenological approach and individual analysis units. The research respondents consist of three high-achieving disabled teenagers aged 16-18 years living in the dormitory of SLB D YPAC Bali. Data were collected through interviews and field notes. The data analysis process used the Interpretative Phenomenological Analysis (IPA) technique. This study reveals how the onset of disability and the surrounding responses become the reasons why teenagers live in dormitories. Hardiness in high-achieving disabled teenagers living in dormitories is formed due to the understanding, accepting, and having self-confidence, becoming independent individuals, and having faith in God influence of social support, the dormitory environment, self-control, self-commitment, and a sense of challenge (3 dimensions of hardiness) within these teenagers.